Exploring the Possibility of Blogging to be Normalized as an Integral Part of Everyday Teaching Practice - Akhmad Affandi; Fauzan Hari Sudding Sally (JTechLP: Journal of Technology in Language Pedagogy, 2022)
The use of technology in everyday teaching practice is commonly seen nowadays. Throughout the span of using computer in Language Teaching, commonly known as computer-assisted language learning (CALL).  Open CALL, which is justified happens nowadays, is determined by the roles of CALL as a simulation, games and computer-mediated communication (CMC). The goal of CALL or various technological product and devices in language learning should be fully integrated where it looks like an ‘invisible' implementation as the technology embedded in every teaching and learning, which means normalization. Therefore, this article explores particularly for blogs as a form of CMC, whether is it feasible to be normalized in everyday teaching practice or not. This article contributes to the rationality that it seems reasonable to conclude blogging is feasible to be normalized in everyday language teaching as long as the issues mentioned by could be resolved. Some steps should be considered which are alterations regarding technology form, approach, and practice among teachers and learners. Its implication is that teaching concept of writing will change to follow asynchronous and synchronous forms of blogs.